Analisa Persepsi Masyarakat Terhadap Pemilihan Produk Pembiayaan Di Bank Syariah Indonesia (Studi Pada Penduduk Desa Bendo Kecamatan Gondang Kabupaten Tulungagung) - Pradana, Okta Wisnu; Khaer, Misbakhul (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to identify and examine the factors that influence the interests of the residents of Bendo Village, Gondang District in utilizing financing services at Bank Syariah Indonesia. The research program used is a qualitative approach using in-depth interviews with the community. The research results show that there are a number of factors that influence the village community's desire to use sharia bank financing services. These factors include understanding of perceptions of sharia principles, trust factors, salaries through sharia banks, limited education and socialization, awareness of the benefits of sharia products. The findings of this research can provide important involvement for more effective marketing and education growth strategies for sharia banks. Indonesia in reaching and growing the desire of village communities to use sharia financing services.